Effects of the Affordable Care Act Medicaid Expansions on Mental Health During the COVID-19 Pandemic in 2020-2021 - Onyinye Oyeka PhD; George L. Wehby PhD (SAGE Publishing, 2023)
To examine whether previous Affordable Care Act (ACA) Medicaid expansions had an added effect on the mental health of low-income adults during the COVID-19 pandemic in 2020 and 2021. We use the 2017-2021 Behavioral Risk Factor Surveillance System (BRFSS) data. We use an event study difference-in-differences model to compare the number of days in poor mental health in the past 30 days and the likelihood of frequent mental distress among 18 to 64 year old individuals with household incomes below 100% of the federal poverty level who participated in BRFSS in one of the surveys from 2017 to 2021 and who resided in states that expanded Medicaid by 2016 or states that had not expanded by 2021. We also examine the heterogeneity of the expansion effects across subpopulation groups. We find some evidence that the Medicaid expansion was associated with better mental health during the pandemic for adults younger than 45, females, and non-Hispanic Black and other non-Hispanic non-White individuals. There is some evidence of an added benefit to mental health from Medicaid expansion status during the pandemic for some subgroups among low-income adults, suggesting potential health benefits from Medicaid eligibility during public health and economic crises.